A mild and effective method for the conversion of alkenes into alcohols in subcritical water - RECEP OZEN (Journal of the Serbian Chemical Society, 2007)
Alkenes were oxidized to alcohols in subcritical water. A number of alkenes were oxidized directly to their alcohols in excellent yields. The syntheses were performed in 215 cm3 stainless steel high pressure reactor at 120 ºC in 150 cm3 water. The yields of alcohols increased with the nitrogen pressure.